Resistência ao riscamento do aço inoxidável ISO 5832-1 nitretado a plasma com fluxo pulsado de nitrogênio - Zarzycki, Ricardo Alex (2022)
Obtaining nitrided layers with different concentrations of nitrogen using plasma nitriding method with pulsed nitrogen flow has been shown to be a promising alternative for surface modification of austenitic stainless steels. In this context, this work evaluated the effect of different concentrations of nitrogen in the nitrided layer of ISO 5832-1 austenitic stainless steel on wear resistance, evaluated by means of a scratch test. Nitriding was performed with pulsed nitrogen flow using two cycles lasting two hours, the first 2P0218, with 10% duty cycle, and the second 2P1010, with 50% duty cycle. During the time the nitrogen gas flow was turned off, the other gasses used in the treatment (hydrogen and argon) remained flowing in the reactor. A plasma nitriding with continuous nitrogen flow (2C), lasting two hours also, was performed for comparison purposes. The samples were subjected to a progressive load and constant load scratching test using Rockwell C geometry diamond tip. The progressive load scratching test used loads from 1 N to 180 N. The constant load scratching test was carried out with a load of 5 N. The scratched samples were analyzed by XRD, SEM and optical interferometry. These analyzes showed that, in all nitriding cycles, there was the presence of double layers (γN/γC) and the γN layer is greater for the highest duty cycles, with 2C being the thickest. The same trend could be observed for the displacement of the austenite peak of the nitrided layer, being it higher for higher duty cycles, the 2C sample showed a greater displacement of the γ austenite peak in the XRD analysis, while 2P0218 showed a smaller peak displacement, indicating for lower nitrogen contents in the layer. Analyzes showed that the volume losses that occurred and the layer thickness removed were significantly different between the samples, with 2C being the one that was the least subject to wear, while 2P0218 had the highest rate of wear. Sample 2P1010 showed intermediate results. From all these analyzes, it was possible to observe that the predominant mechanism in the wear of the nitrided layers was micro grooving instead of micro cutting, since the plastic deformation of the layers is more present than the removal of material.